2017
DOI: 10.1002/prep.201700143
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics and Thermal Decomposition Behaviors of Polytetrahydrofuran Binder with Glycerol Propoxylate (Mn=1500) as a Crosslinking Agent

Abstract: Polytetrahydrofuran (PTHF) is an effective binder ingredient for improving propellant performance, although it is not an energetic material. PTHF becomes sufficiently rubbery for use as a binder when a triol is added as a crosslinking modifier. In this study, glycerol propoxylate (GPO), with a molecular weight of 1500, was used as a crosslinking modifier, and the curing behavior, tensile properties, and thermal decomposition behaviors of the PTHF binder with GPO were investigated. A PTHF (M n = 650)/GPO blend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The network density of a cross‐linked polymer was estimated by the degree of swelling by an appropriate solvent at equilibrium. A swelling test was conducted using a rectangular parallelepiped sample (20 mm×20 mm×2 mm) at 298 K. Toluene was used as the swelling solvent [12–15]. The mass of the sample was measured before and after immersion in toluene, and the volumes were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The network density of a cross‐linked polymer was estimated by the degree of swelling by an appropriate solvent at equilibrium. A swelling test was conducted using a rectangular parallelepiped sample (20 mm×20 mm×2 mm) at 298 K. Toluene was used as the swelling solvent [12–15]. The mass of the sample was measured before and after immersion in toluene, and the volumes were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In other studies, glycerol propoxylate (GPO) was used as a crosslinking modifier (see Figure 1 for chemical structure) for the PTHF binder [14, 15]. GPO is a triol material with a zigzag structure, and it has one oxygen atom in a repeating unit.…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrahydrofuran (PTHF) based propellant produce promising mechanical properties while having better oxygen balance and higher burn rate than HTPB [57][58][59][60]. In fact, in a propellant of 80% ammonium perchlorate to 20% binder by weight mixture, directly replacing HTPB with PTHF results in a 10-second increase in specific impulse.…”
Section: Other Energetic Bindersmentioning
confidence: 99%
“…Although PTHF does not contain any energetic components, it gives a specific impulse comparable to that of energetic polymers due to its higher oxygen balance than HTPB [58][59][60]. Kohga and his team have been testing various formulations of PTHF and has shown that certain ammonium perchlorate-PTHF-based formulation has nearly twice the burn rate of HTPB-based propellant [57].…”
Section: Other Energetic Bindersmentioning
confidence: 99%
See 1 more Smart Citation